แผนงานวิจัย นโยบายและกลยุทธ์เพื่อการท่องเที่ยววิถีวัฒนธรรมมลายูในเขตเศรษฐกิจพิเศษสงขลา - ปาริชาติ วิสุทธิสมาจาร (มหาวิทยาลัยสงขลานครินทร์, 2024)
This research project aims to: 1) study the situation, problems and impacts on tourism in Songkhla Special Economic Zone to cope with the ASEAN economic liberalization. 2) analyse study result to conduct a tourism plan in the Songkhla Special Economic Zone to cope with the ASEAN economic liberalization , and 3) to conduct tourism policy and strategies for Melayu’s cultural tourism in the Special Economic Zone of Songkhla. Scope of the research area covered 4 sub-districtsl; namely Sumnaktaw, Sumnakkham, Padangbeza, and Sadao sub-districts, Songkhla province. Research methodology covered quantitative and qualitative analysis with focus group meeting, in-depth interview and content analysis. Result of the three sub-projects together with the determination of tourism development strategies, taking into account the 4 dimensions according to the principles of the Balanced Scorecard, which has a framework for analyzing both strategies, namely the strategy to upgrade quality And potential enhancement strategies Which has been analyzed Assessment of tourism readiness and SWOT analysis of tourist attractions In creating a framework for strategic tourism development aimed at qualitative and sustainable tourism Therefore, this research plan has issued the five policies and 19 strategies. Each policy will focus on different goals. In general, the proposed strategy into three areas: 1) development and promotion, 2) restoration and conservation, 3) confidence building, and 4) human capacity building and management. Policies are included; 1) the development of Melayu’s cultural tourism resources, 2) the restoration of the Melayu’s culture for tourism management, 3) the development and promotion of tourism for Melayu’s culture, 4) confidence building for border tourism , and 5) Develop human capacity building and integrated management to ASEAN. For tourism model should apply the cultural tourism management which combines two concepts; experience based tourism, and presenting new charm. This provides three types learning experience; 1) identity of Melayu culture 2) increase interpretation of Melayu’s culture 3) good hospitality of creative tourism management for accommodation and food. Whereas, presenting new charms of the area could be 1) zoning of Melayu’s